Keharusan Ikrar Talak di Depan Majelis Hakim Pengadilan Agama : Perspektif Maqāṣid Syarī’ah Ibnu ‘Āsyūr - ludfi (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
This study aims to elaborate on the provisions of divorce in classical fiqh which are considered valid simultaneously when pronounced by the husband, while in positive law they are only considered valid when pronounced by the husband before the court. Both of them gave rise to a